Influence of the Neonicotinoid Insecticide Thiamethoxam on miRNA Expression in the Honey Bee (Hymenoptera: Apidae). Issue 5 (2nd October 2017) - Shi, Teng-Fei; Wang, Yu-Fei; Liu, Fang; Qi, Lei; Yu, Lin-Sheng
Abstract: MicroRNAs (miRNAs) are small endogenous noncoding single-stranded RNAs regulating gene expression in eukaryotes. They play important roles in regulating caste differentiation, behavior development, and immune defences in the honey bee, Apis mellifera (Linnaeus) (Hymenoptera: Apidae). In this study, we explored the effect of the neonicotinoid insecticide, thiamethoxam, on miRNA expression in this species using deep small RNA sequencing. The results showed that seven miRNAs were significantly differentially expressed ( q -value <0.01 and |log2 (fold-change)| >1) upon exposure to 10 ppb thiamethoxam over 10 d. Some candidate target genes were related to behavior, immunity, and neural function. Several miRNAs, including ame-miR-124, ame-miR-981, ame-miR-3791, and ame-miR-6038, were selected and further validated using real-time quantitative PCR analysis. The findings expand our understanding of the effects of neonicotinoid insecticides on honey bees at the molecular level.